2019
DOI: 10.3390/ijms20122985
|View full text |Cite
|
Sign up to set email alerts
|

An Inactivation Switch Enables Rhythms in a Neurospora Clock Model

Abstract: Autonomous endogenous time-keeping is ubiquitous across many living organisms, known as the circadian clock when it has a period of about 24 h. Interestingly, the fundamental design principle with a network of interconnected negative and positive feedback loops is conserved through evolution, although the molecular components differ. Filamentous fungus Neurospora crassa is a well-established chrono-genetics model organism to investigate the underlying mechanisms. The core negative feedback loop of the clock of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 86 publications
0
19
0
Order By: Relevance
“…Bifurcation analyses on a manifold of clock models have shown that parameter changes can lead to transitions between stable equilibrium points and periodic limit cycle oscillations [ 41 , 74 , 75 ]. In this study, we have found that more complex bifurcations, such as subcritical Hopf bifurcations, period-doubling cascades that lead to chaos or bifurcations that result in toroidal oscillations, can occur in simple, yet comprehensive models of the mammalian circadian clock.…”
Section: Discussionmentioning
confidence: 99%
“…Bifurcation analyses on a manifold of clock models have shown that parameter changes can lead to transitions between stable equilibrium points and periodic limit cycle oscillations [ 41 , 74 , 75 ]. In this study, we have found that more complex bifurcations, such as subcritical Hopf bifurcations, period-doubling cascades that lead to chaos or bifurcations that result in toroidal oscillations, can occur in simple, yet comprehensive models of the mammalian circadian clock.…”
Section: Discussionmentioning
confidence: 99%
“…We emphasize, that our focus on multiple random phosphorylations neglects other essentials of the TTFL modeled in detail elsewhere 26,80,90,91 . Nevertheless, delayed switch-like behavior due to slow random multiple phosphorylation seems to be central element in circadian rhythm generation.…”
Section: Discussionmentioning
confidence: 99%
“…We emphasize, that our focus on multiple random phosphorylations neglects other essentials of the transcriptional-translational feedback loop (TTFL) modeled in detail elsewhere [26,[75][76][77][78]. Nevertheless, delayed switch-like behavior due to slow random multiple phosphorylation seems to be central element in circadian rhythm generation.…”
Section: Discussionmentioning
confidence: 99%